Study on Relationship of the Resistivity with Specific Heat - Hernández, Alfredo Olmos; Hernández, Reyna Romyna Olmos (Issues and Developments in Medicine and Medical Research Vol. 8, 2022)
We study the relationship between resistivity and specific heat. It is known that the resistivity of a conductor increases when its temperature increases. And the specific heat of a material is found as a function of temperature, so we calculated the resistivity from the specific heat and the temperature variation. The resistivity of a conductor is determined as a function of specific heat, the resistance of a conductor is determined as a function of mass, temperature and specific heat; and the electric field is determined as a function of the specific heat.